The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep29941
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation network with pair-coupling structure in {111} γ/γ′ interface of Ni-based single crystal superalloy

Abstract: The γ/γ′ interface dislocation network is reported to improve the high temperature creep resistance of single crystal superalloys and is usually found to deposit in {001} interface. In this work, a new type of dislocation network was found in {111} γ/γ′ interface at a single crystal model superalloy crept at 1100 °C/100 MPa. The dislocations in the network are screw with Burgers vectors of 1/2 a<110> and most interestingly, they exhibit a pair-coupling structure. Further investigation indicates that the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 37 publications
(72 reference statements)
0
14
0
Order By: Relevance
“…But, when a succeeding dislocation shears the ordered phase again, the original symmetry of the ordered phase can be restored. Therefore, they suggested that the pairs of dislocations, called as superdislocations, should glide together at the slip band front to avoid the formation of the APB 31,43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…But, when a succeeding dislocation shears the ordered phase again, the original symmetry of the ordered phase can be restored. Therefore, they suggested that the pairs of dislocations, called as superdislocations, should glide together at the slip band front to avoid the formation of the APB 31,43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…dislocations have been observed by Ru et al [36] following isothermal creep at 1100°C and 100 MPa. However, the dislocation configuration observed by Ru et al [36] was identified as pure screw dislocations.…”
Section: B Dislocation Structures In the Falling Strain Rate Regimementioning
confidence: 80%
“…A higher misfit thus results in a denser interfacial dislocation network. In the case of Ru et al, [36] the paired dislocation network formed during isothermal creep in a 4th generation superalloy with a high misfit. Le Graverend et al showed that similarly high misfit magnitudes could be achieved during short high-temperature excursions.…”
Section: A the Effect Of Interfacial Dislocation Network During Cycmentioning
confidence: 99%
“…Mughrabi ascribes this deterioration to a rapid increase in deformation induced by internal stresses, which cannot be released any longer by the interface dislocations once the ␥ phase is being split into discrete islands [38]. Other studies [33,39,40] have indicated that in the inversed microstructure the shape of ␥/␥' interfaces changes from smooth into zigzag, leading to the formation of new dislocation glide planes in ␥', which correspondingly promote the formation of dislocation pile-ups and consequently cutting of the ␥' phase.…”
Section: Break-up Stagementioning
confidence: 99%
“…Experimental results have shown that the {111}-type distorted interface forms as a consequence of the inversed microstructure [73,74,77]. The zigzag interface forms through dislocations which cut into the ␥'raft via {111} planes of interface [40]. The accelerated creep rate can then be attributed as the increased dislocation activity with the break-down of dislocation networks and the formation of new gliding planes.…”
Section: Break-up Of Interfacial Dislocation Structurementioning
confidence: 99%